Jaridah Al-Kashshaf : (Al-jam'iyyah al-misriyyah li al-dirasat al-tarikhiyyah, 1978)
'The Kashshaf newspaper : (1927-28) study and analysis' Reprint : Al-majallah al-tarikhiyyah al-Misriyyah (1978):no.25, p.205-230.